Logics with probabilistic team semantics and the Boolean negation - Hannula, Miika; Hirvonen, Minna; Kontinen, Juha; Mahmood, Yasir; Meier, Arne; Virtema, Jonni (Journal of Logic and Computation)
Abstract We study the expressivity and the complexity of various logics in probabilistic team semantics with the Boolean negation. In particular, we study the extension of probabilistic independence logic with the Boolean negation, and a recently introduced logic first-order theory of random variables with probabilistic independence. We give several results that compare the expressivity of these logics with the most studied logics in probabilistic team semantics setting, as well as relating their expressivity to a numerical variant of second-order logic. In addition, we introduce novel entropy atoms and show that the extension of first-order logic by entropy atoms subsumes probabilistic independence logic. Finally, we obtain some results on the complexity of model checking, validity and satisfiability of our logics.

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.

Machine-Learning basierte Analyse von latenten Profilen des physikdidaktischen Wissens Machine-Learning-Based Analysis of Latent Profiles in Physics PCK - Zeller, Jannis; Riese, Josef (Zeitschrift für Didaktik der Naturwissenschaften)
Das fachdidaktische Wissen (FDW) stellt eine wichtige Komponente des Professionswissens von (angehenden) Lehrkräften dar. Es liegen bereits empirische Forschungsergebnisse zu Einflussfaktoren und zur Entwicklung des FDW sowie zur Bedeutung des FDW als Ganzem für Professionswissen und Qualität professioneller Handlungen vor. Für eine detailliertere Forschung zur Zusammenhangsstruktur zwischen FDW und der Performanz in prototypischen Handlungssituationen sind darüber hinaus differenziertere empirisch begründete Beschreibungen der inneren Struktur des FDW notwendig. Bisher sind entsprechende Ansätze allerdings zumeist primär theoretisch-normativ begründet oder auf hierarchische Betrachtungen beschränkt. Im vorliegenden Beitrag wird daher ein Ansatz zur nicht-hierarchischen datenbasierten Beschreibung latenter Kompetenzprofile des FDW orientiert an der Computational Grounded Theory vorgestellt. Dabei wird zunächst mithilfe eines Datensatzes von 846 Bearbeitungen des Physik-FDW-Testinstruments in überwiegend offenem Antwortformat aus dem Projekt ProfiLe-P+ eine latente Profilanalyse zur Untersuchung latenter FDW-Profile unter Fokus auf kognitive Anforderungen als empirisch trennbare Subskalen des FDW durchgeführt. Mithilfe von Topic Modeling werden anschließend Tendenzen in der Sprachnutzung der FDW-Profile untersucht. Um die Ergebnisse im Sinne der Computational Grounded Theory durch den Nachweis latenter Zusammenhänge zwischen den Testantworten der Proband:innen und der FDW-Profil-Zuordnung zu bestätigen, wird im Anschluss ein Machine-Learning-basiertes System zur automatisierten Zuordnung von Testbearbeitungen zu den FDW-Profilen erstellt. Es zeigen sich vier latente Kompetenzprofile mit nicht-hierarchischem Charakter. In einer längsschnittlichen Betrachtung wird abschließend die Entwicklung von Proband:innen im Kontext dieser FDW-Profile dargestellt. Die Ergebnisse bieten Ansatzmöglichkeiten zukünftig Untersuchungen der Zusammenhänge einzelner FDW-Komponenten und beispielsweise gezeigter Handlungsqualität auf Detailebene zu untersuchen.

Maddy, Penelope, Jouko Väänänen, Philosophical Uses of Categoricity Arguments, Cambridge University Press: Cambridge 2023 (Cambridge Elements). - Peckhaus, Volker (zbMATH Open, Zbl. 07771690)

Mastering Temporal Challenges – Zeitwohlstand und Zeiterleben iranischer Studierender in Deutschland - Philipper, Matthias (Geschlecht und Gerechtigkeit)

Materialien zum Schreiben im Psychologieunterricht - Scharlau, Ingrid; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Mathematics education for girls in Prussia 1890–1925 - Krüger, Katja; Werth, Gerda (The Journal of Mathematical Behavior)

Mathematikbezogenes Wissen, Einstellungen und Lerngelegenheiten als Einflussfaktoren der situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachkräfte - Quack, Carolin; Bruns, Julia (Frühe Bildung)

Mathematische Grundbildung und rechnerische Grundkompetenzen im Feld der „Berufsbildung“ - Heisler, Dietmar; Sommer, Christian (Grundbildung und Habitus)
Zusammenfassung Für die Erklärung von sozialer Ungleichheit und des Einflusses sozialer Herkunft auf die Bildungsteilhabe von Individuen, auf ihre Bildungsbeteiligung und ihren Bildungserfolg wird oft auf die kultur- und bildungssoziologischen Ansätze Pierre Bourdieus zurückgegriffen. Dies gilt auch für den Bereich der Grundbildung, für die Erklärung von individuellen Leistungsunterschieden im Lesen, Schreiben und Rechnen. Unterschiede bei der Bildungsteilhabe und im Bildungserfolg werden von ihm u. a. auf die soziale Herkunft und die sozialen Praktiken in den sozialen Milieus zurückgeführt. Gerade Bourdieu versucht auch zu erklären, wie konkrete Anforderungen und Bildungsinhalte den Weg in schulische Curricula finden und so in Wechselwirkung mit den Strukturen des Bildungswesens und seinen sozialen Praktiken zur Reproduktion sozialer Ungleichheit in der Gesellschaft beitragen. Die These ist, dass die Inhalte und auch die Strukturen des Bildungswesens von einer bildungsnahen sozialen Oberschicht bestimmt werden, was den Bildungserfolg der Angehörigen dieser Schicht begünstigt und im Weiteren zur Reproduktion der Unterschiede zwischen den sozialen Milieus beiträgt. Der vorliegende Beitrag übersetzt dies in den Bereich der Grundbildung, vor allem der mathematischen Grundbildung und Vermittlung basaler mathematischer Grundkompetenzen. Ausgangspunkt ist die Frage, was unter mathematischer Grundbildung verstanden wird. Dafür wurden 21 Berufsschullehrkräfte in Interviews befragt. Die Ergebnisse der Befragung zeigen, dass mathematische Grundbildung von den Lehrkräften zu den Anforderungen von Bildungsgängen und Berufen kontextualisiert bzw. in Relation gesetzt wird. Als mathematische Grundkompetenzen werden Wissen und Fähigkeiten verstanden, die notwendig sind, um einen gegenwärtigen Bildungsgang bewältigen zu können, und die in vorangegangenen Bildungsgängen erworben wurden. Folglich werden mathematische Grundkompetenzen, die für die Bewältigung beruflicher Bildungsgänge notwendig sind, an den Klassenstufen im allgemeinbildenden Schulsystem festgemacht, deren Inhalte für den jeweiligen Bildungsgang als Voraussetzung oder grundlegend zur Bewältigung seiner Anforderungen und Inhalte betrachtet werden. Das hat zur Folge, dass es zum einen kein einheitliches Verständnis zu mathematischer Grundkompetenz bzw. sogenannten basalen Rechenfähigkeiten gibt. Vielmehr werden diese an unterschiedlichen Klassenstufen und Leistungsniveaus festgemacht. Unter Rückgriff auf die Überlegungen Bourdieus bedeutet dies zum anderen, dass die beruflichen Schulen die soziale und herkunftsbedingte Selektivität, die bislang vor allem am allgemeinbildenden Schulsystem kritisiert wird, über ihre Bildungsgänge fortschreiben, indem aus den Bildungsgängen heraus formale und inhaltliche Anforderungen formuliert werden, die den konkreten Bezug zu bestimmten Klassenstufen und Schulformen nehmen. Dies kann nun als Ausdruck oder Hinweis auf die Selektions- und Allokationsfunktion von Schule interpretiert werden. Allerdings erscheint es insofern kritisch, da die beruflichen Schulen seit ihren Reformen in den 1970er Jahren doch den Anspruch erheben, deutlich durchlässiger und weniger sozial selektiv zu sein als die allgemeinbildenden Schulen.

Maximizing the benefits of student-generated drawing for real-world problem solving - Schönherr, Johanna; Mayer, Richard E. (Contemporary Educational Psychology)

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, M.; Holtkamp, P.-K.; Hoyer, K.-P.; Kappe, F.; Yildiz, S.; Bobbert, M.; Meschut, G.; Schaper, M. (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
One of the most important strategies for reducing CO 2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Mee To in Science. Sexualisierte Diskriminierung und Gewalt an Hochschulen.

Mehrebenenannotation argumentativer Lerner*innentexte für die automatische Textauswertung - Rezat, Sara; Kilsbach, Sebastian; Michel, Nadine; Karabey, Rabia; Stahl, Maja; Wachsmuth, Henning (Zeitschrift für Angewandte Linguistik)

mei-friend: An Interactive Web-based Editor for Digital Music Encodings (1.2.0) - Goebl, Werner; Weigl, David M.; Plaksin, Anna Viktoria Katrin
This release contains two new major features and several smaller improvements: Extension of mei-friend's facilities for editorial mark-up through a re-worked annotation panel (now renamed to enrichment panel). Thanks to @annplaksin! See documentation at https://mei-friend.github.io/docs/advanced/markup/. Redevelopment of git integration for more stable and sustainable collaborative editing. For more information, please see CHANGELOG.md

Meine Schwangerschaft - so individuell wie ich! - Schneider, Tamara; Weber, Julia

Metaphors for explaining - a short guide - Scharlau, Ingrid; Porwol, Philip
Künstliche Intelligenz oder auch einfach Erklären - verwenden sie absichtlich oder unabsichtlich Metaphern. Diese Metaphern können beeinflussen, wie die Sprecher*innen und Hörer*innen über das Thema denken und wie sie handeln. So können beispielsweise Erklärmetaphern beeinflussen, wie Wissenschaftler*innen erklärende technische Systeme entwerfen. Dieser Artikel soll die Aufmerksamkeit auf Metaphern und ihre möglichen Folgen lenken. Darüber hinaus beschäftigen wir uns mit verbreiteten spezifischen Erklärungsmetaphern beschäftigen und machen Vorschläge , welche Metaphern zum Verständnis des Erklärens im Rahmen des Sonderforschungsbereichs „Constructing Explainability“ passen bzw. nicht passen und was bei der Verwendung von Metaphern zu beachten ist.

Metaphors in 24 WIRED Level 5 Videos (Data corpus) - Scharlau, Ingrid